2020
DOI: 10.1111/ahg.12374
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction Statement: Inhibition of miR‐499‐5p expression improves nonalcoholic fatty liver disease

Abstract: Objective: Nonalcoholic fatty liver disease (NAFLD) is one of the leading causes of chronic liver diseases. However, the pathogenesis of NAFLD is largely unknown.Here, we investigated the specific role of miR-499-5p in NAFLD. Methods:Free fatty acid was used to induce HL-7702 cell line to establish a NAFLD cell model, and animal models of NAFLD were constructed by feeding C57BL/6 mice with a high-fat diet. Expression levels of miR-499-5p in the HL-7702 cells and C57BL/6 mice were determined by quantitative rea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Furthermore, miR-499 genetic variation has also been reported as a crucial indicator of diabetic neuropathy susceptibility and could indicate patients with a higher risk of developing cardiovascular autonomic neuropathy [76]. Recently, a link between miR-499 and NAFLD was also discovered, as it was demonstrated by Hanyun et al [77] that miR-499 inhibition improves NAFLD which, as was previously mentioned, is often associated with insulin resistance. The experimental model involved specific pathogen-free (SPF) male C57BL/6 mice fed with a high-fat diet and injected with an miR-499 inhibitor.…”
Section: Mir 499-5pmentioning
confidence: 84%
“…Furthermore, miR-499 genetic variation has also been reported as a crucial indicator of diabetic neuropathy susceptibility and could indicate patients with a higher risk of developing cardiovascular autonomic neuropathy [76]. Recently, a link between miR-499 and NAFLD was also discovered, as it was demonstrated by Hanyun et al [77] that miR-499 inhibition improves NAFLD which, as was previously mentioned, is often associated with insulin resistance. The experimental model involved specific pathogen-free (SPF) male C57BL/6 mice fed with a high-fat diet and injected with an miR-499 inhibitor.…”
Section: Mir 499-5pmentioning
confidence: 84%
“…miR-133a could inhibit the browning of adipocytes [ 19 ], which may partly decrease adipocyte loss. Inhibition of miR-499-5p expression in mice with nonalcoholic fatty liver could reduce the accumulation of lipid and triglyceride and reduce total cholesterol in serum in individual mice [ 20 ]. miR-133a-5p was down-regulated in subcutaneous fat deposition in rats fed high-fat diet (HFD), but up-regulated in HFD mice [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have reported that miRNAs are involved in the development of intramuscular preadipocytes [ 57 , 58 ], the molecular regulation mechanism of miRNAs in porcine IMF development remains largely unknown. Studies have shown that inhibition of ssc-miR-499-5p expression in nonalcoholic fatty liver disease ( NAFLD ) cells reduces lipid deposition and of triglyceride (TG) content [ 59 ]. However, in this study, ssc-miR-499-5p was upregulated in high-IMF animals, which may be due to the high conservation and tissue specificity of miRNA, which plays different roles in different tissues.…”
Section: Discussionmentioning
confidence: 99%